Pond-Based Scientific Approach and Learning Motivation on Student Learning Outcomes - Basruddin, Basruddin; Devilla, Rego; Saripuddin, Saripuddin; Syarif, Muqtakdir Nurfalaq; Putera, Wahyudi (Indonesian Journal of Education and Mathematical Science, 2024)
The pond-based scientific approach is a scientific approach for students in the aquaculture area, which requires the support of local wisdom-based learning media. With the many scientific approaches that exist, it does not make it difficult for students to raise local wisdom, namely aquaculture, to be used as research in obtaining student learning outcomes. The scientific approach can also provide learning motivation to students so that students are motivated to study harder in lifting student learning outcomes. This study aims to determine the literature review related to the pond-based scientific approach and learning motivation in improving student learning outcomes. The research method chosen is descriptive quantitative by first testing validity, reliability, classical assumptions, partial (t) and simultaneous (f) testing using the help of SPSS Ver,- 2023 software for windows. Data collection was carried out by interview, documentation and questionnaires distributed to respondents who had a population of 200 respondents of SDN 37 Bulu-Bulu, Pangkajene District and the sample was taken by random sampling using 15% of the population totaling 30 respondents of SDN Bulu-bulu students, Pangkajene District, Pangkep Regency. The results of the study partially test or test (t) and simultaneous test (f) pond-based scientific approach has a significant effect on student learning outcomes SDN 37 Bulu-bulu Pangkajene District Pangkep Regency. Then the partial test or test (t) or simultaneous test (f) student learning motivation has a significant effect on the learning outcomes of students of SDN 37 Bulu-bulu, Pangkajene District, Pangkep Regency.